Molecular assessment of minimal residual disease in PBSC harvests provides prognostic information in neuroblastoma. Issue 9 (21st March 2013) - Chambon, F.; Tchirkov, A.; Pereira, B.; Rochette, E.; Deméocq, F.; Kanold, J.
Abstract As almost all patients with high‐risk neuroblastomas have autograft, we aimed to determine if minimal residual disease (MRD) quantified by RT‐PCR for tyrosine hydroxylase in PBSC is prognostic in neuroblastomas. PBSC harvests from 38 children were analyzed. Seven had harvests positive for TH‐mRNA. Patients with a positive MRD had a lower 2‐year‐overall‐survival compared to those with negative MRD (P = 0.04) regardless of whether or not PBSC were re‐infused. Patients in CR/VGPR group with positive MRD have hazard ratio of death at 7.3 [1.3–40.5]. In conclusion, molecular MRD status in PBSC of good response group may be of interest as a survival prognostic factor in high‐risk neuroblastomas. Pediatr Blood Cancer 2013;160:E109–E112. © 2013 Wiley Periodicals, Inc.